77.8k views
5 votes
Write each term needed to find the sum and then find the sum.

Write each term needed to find the sum and then find the sum.-example-1
User Oscarmlage
by
6.1k points

1 Answer

4 votes

Given the sum:


\sum ^5_(i\mathop=0)(i-3)^2

We will write each term needed to find the sum.

We will substiute with ( i = 1, 2, 3, 4, 5 ) into the given expression.

There are five terms as follows:


\begin{gathered} a_1=(1-3)^2=(-2)^2=4 \\ a_2=(2-3)^2=(-1)^2=1 \\ a_3=(3-3)^2=(0)^2=0 \\ a_4=(4-3)^2=(1)^2=1 \\ a_5=(5-3)^2=(2)^2=4 \end{gathered}

The sum will be =


\sum ^5_(i\mathop=1)(i-3)^2=4+1+0+1+4=10

User Oleg Karasik
by
6.0k points